Study of Social Carrying Capacity in The Development of Tanjung Lesung as a Sustainable Tourist Destination - Yunita Ismail; Tiara Widhi (AIBPM Publisher, 2022)
ABSTRACTTanjung Lesung is one developing tourism destination, that prepares infrastructure for accessibility. It is in Tanjung Jaya village and is an agricultural area, with people whose main livelihood is from the agricultural sector. The change in the community's main livelihood from agriculture to the tourism industry requires community development and assistance. This study aims to provide an overview of the socio-economic aspects of the Tanjung Lesung community and provide an overview of tourism development. Qualitative methods were used in this paper, using deliberate sampling, interviews, and observations. The field observations found that the people of Tanjung Lesung are an agricultural community that has begun to shift to tourism businesses. For people's livelihoods, they have tried to start doing business in the tourism industry, especially with the support from the Cikadu Edutourism Center.Keywords: Social Economy, Tourism Development, Tourist Destination, Agriculture